2014
DOI: 10.1590/1519-6984.10512
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation of leaf litter by aquatic invertebrates in an Atlantic Forest stream

Abstract: Riparian vegetation along streams in the Atlantic Forest in Brazil contributes to the formation of a highly heterogeneous leaf litter in streambeds. To investigate the structure and composition of the aquatic invertebrate community during the process of leaf decomposition of two plant species present along the banks of the stream studied, 21 plastic mesh bags containing 2.5g (dry weight) of leaf matter from each species (Alchornea glandulosa (Vell) and Cabralea canjerana End. and Poeppig), for a total of 5.0g,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(26 reference statements)
1
4
0
1
Order By: Relevance
“…In this study, the k values (pools: k  = 0.013 d; riffles: k  = 0.021 d) were low in comparison to recorded k values for leaf breakdown of high nutritional quality from the Atlantic Rain Forest: Piper divaricatum (Piperaceae; k  = 0.182 d), Campomanesia xanthocarpa (Myrtaceae; k  = 0.052 d), Myrcia rostrata (Myrtaceae; k  = 0.042 d), and Cupania vernalis (Sapindaceae; k  = 0.037 d; see Moulton and Magalhães 2003, Tonin et al 2014). Moreover, in this same Brazilian biome, our k values was similar to those of Erythrina verna (Fabaceae; k  = 0.0202 d), M. rostrata (Myrtaceae; k  = 0.019 d) and leaf mixtures from Alchornea glandulosa and Cabralea canjerana (Euphorbiaceae and Meliaceae; k  = 0.028 d; see Moulton et al 2010, Gonçalves et al 2012b, Oliveira et al 2014). These species have low hardness and high values of N and P compared to plants of other biomes, such as the Brazilian cerrado.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, the k values (pools: k  = 0.013 d; riffles: k  = 0.021 d) were low in comparison to recorded k values for leaf breakdown of high nutritional quality from the Atlantic Rain Forest: Piper divaricatum (Piperaceae; k  = 0.182 d), Campomanesia xanthocarpa (Myrtaceae; k  = 0.052 d), Myrcia rostrata (Myrtaceae; k  = 0.042 d), and Cupania vernalis (Sapindaceae; k  = 0.037 d; see Moulton and Magalhães 2003, Tonin et al 2014). Moreover, in this same Brazilian biome, our k values was similar to those of Erythrina verna (Fabaceae; k  = 0.0202 d), M. rostrata (Myrtaceae; k  = 0.019 d) and leaf mixtures from Alchornea glandulosa and Cabralea canjerana (Euphorbiaceae and Meliaceae; k  = 0.028 d; see Moulton et al 2010, Gonçalves et al 2012b, Oliveira et al 2014). These species have low hardness and high values of N and P compared to plants of other biomes, such as the Brazilian cerrado.…”
Section: Discussionsupporting
confidence: 70%
“…According to Alves et al (2008), Petsch et al (2015), Maroneze et al (2011) and Ragonha et al (2014), these organisms can be found living on sandy substrates or in organic matter enriched environments (Behrend et al, 2012). In addition, these organisms are also recorded associated with aquatic macrophytes and leaf litter (Trivinho-Strixino et al, 2000;Alves and Gorni, 2007;Gorni and Alves, 2007;Oliveira et al, 2014) with sponges (Gorni and Alves, 2008) gastropods (Gorni and Alves, 2006), insect larvae (Corbi et al, 2004) and amphibians (Oda et al, 2015). Recent studies (Gorni et al, 2015) recorded 75 species of aquatic oligochaetes in the State of São Paulo, in which 64 species (85%) belong to the Naididae family.…”
Section: (With 1 Figure)mentioning
confidence: 99%
“…We buried a metal chamber base y 180 mm diameter in the stream sediments (two per habitat -randomly placed). A sample of intact substrate was removed from the river bottom and gently placed on the base, where it was left submerged in the stream for 3-5 days to allow macroinvertebrates recolonization (assuming that previous studies at perennial streams of O 'Connor, 1991;Boyero, 2003;Oliveira et al, 2014 will be similarly applicable to our system). In most benthic community studies, the bases were left for longer periods (Bott et al, 1978).…”
Section: Study Sitementioning
confidence: 99%